Impacts of Betaine Addition in Sow and Piglet's Diets on Growth Performance, Plasma Hormone, and Lipid Metabolism of Bama Mini-Pigs - Cheng, Yating; Song, Mingtong; Zhu, Qian; Azad, Md. Abul Kalam; Gao, Qiankun; Kong, Xiangfeng (Frontiers in Nutrition, 2021)
The present study evaluated the effects of betaine addition in sow and piglet's diets on growth performance, plasma hormone, and lipid metabolism of Bama mini-pigs. A total of 26 pregnant Bama mini-pigs and 104 weaned piglets were selected and divided into different dietary treatment groups (details in “Materials and Methods”). Blood and muscle samples were collected at 65-, 95-, and 125-day-old, respectively. The results showed that betaine addition in sow-offspring diets increased (P < 0.05) the body weight at 125-day-old, average daily gain from 35- to 65-day-old, and average daily feed intake at 35–65 and 35–95 days old of pigs compared with the control group. Betaine addition in sow-offspring diets increased (P < 0.05) the plasma gastrin level at 95-day-old, while betaine addition in sow diets decreased (P < 0.05) the plasma peptide YY and leptin levels at 65-day-old pigs. In the longissimus dorsi muscle of pigs, betaine addition in sow and sow-offspring diets increased (P < 0.05) the C12:0 content at 65-day-old while decreased at 95-day-old. Moreover, betaine addition in sow-offspring diets increased the C24:0 content and decreased the C18:1n9t content at 125-day-old (P < 0.05). In the biceps femoris muscle, the contents of C12:0 at 65-day-old and C20:4n6 at 125-day-old were decreased (P < 0.05) after the betaine addition in both sow and piglet's diets. In addition, betaine addition in sow diets decreased (P < 0.05) the C20:0 content at 125-day-old, while betaine addition in sow-offspring diets increased the C18:3n6 and decreased C24:0 contents at 65-day-old pigs (P < 0.05). In the psoas major muscle, betaine addition in sow and sow-offspring diets decreased (P < 0.05) the contents of C18:1n9t at 65-day-old and C20:1 at 95-day-old, while betaine addition in sow diets decreased (P < 0.05) the intramuscular fat content at 125-day-old. Moreover, betaine addition in sow-offspring diets was also associated with muscle lipid deposition and metabolisms by regulating the gene expressions related to fatty acid metabolism. These findings suggested that betaine addition in sow-offspring diets could improve the growth performance, whereas betaine addition in both sow and sow-offspring diets could enhance lipid quality by altering plasma hormone level and fatty acid composition and regulating the gene expressions related to fatty acid metabolism.